Distribution of ectoparasites among dogs of different populations in the Kharkiv region - Kiptenko, A.; Bogach, М. (Scientific Progress & Innovations, 2025)
Parasitic diseases constitute a significant share in the overall structure of infectious morbidity among both farm and domestic animals. In recent years, there has been a significant increase in the number of both domestic and stray animals, which, in turn, has led to an increase in epizootological risk and the active spread of invasive pathology, in particular ectoparasitoses. Among ectoparasitic diseases in dogs and cats, tick-borne dermatitis, the etiological agents of which are Otodectes cynotis ticks, representatives of the Ixodidae family (ixodus ticks), as well as sarcoptic mange pathogens, poses a particular epizootological and clinical threat. These parasites cause significant pathological changes in the skin, accompanied by intense itching, allergic reactions and secondary bacterial infections, which complicates the course of the disease. The dynamics of parasitic invasions in these animals largely depend on a complex of biotic factors (interaction between species, immune status of the animal). A collection of fleas of the species Ctenocephalides felis was carried out by combing the animals with a special fine-toothed plastic comb in five anatomically defined areas. Ixodes spp. ticks detected during clinical examination were removed from the skin of the animals using anatomical tweezers in compliance with the rules of asepsis. Diagnosis of Otodectes cynotis was carried out by visualization of live ticks using otoscopic examination, as well as microscopic examination of smears taken from the external auditory canal. The total infestation of dogs varied depending on the population: in homeless dogs ‒ 100%, in rural dogs ‒ 64.3 %, in urban dogs ‒ 50.9 %. In urban dogs, the most common parasite was Otodectes cynotis (29.6 %), in homeless dogs ‒ Ctenocephalides canis (36.7 %) and mixed infestations (15.6%), in rural dogs, Ctenocephalides canis (21.1 %) and Ixodes spp. (19.4 %) prevailed. The intensity of the lesion ranged from 5.9 to 27.6 specimens/head. The high frequency of infestations, especially among stray animals, indicates the lack of prevention and epizootic danger. The results of the study indicate the dependence of the level of infestation on the conditions of keeping dogs. The highest threat is posed by stray animals, which are an active source of the circulation of ectoparasites. The data obtained emphasize the need for the implementation of systematic prevention of ectoparasites, especially in urban areas, where contact between animal populations is most likely.